1997
DOI: 10.1017/s0022029997002252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yogurt and bifidus yogurt fortified with skim milk powder, condensed whey and lactose-hydrolysed condensed whey on serum cholesterol and triacylglycerol levels in rats

Abstract: The possible hypocholesterolaemic properties of milk and fermented milk products have been investigated in groups of albino rats given a basal diet, basal diet plus cholesterol, and basal diet plus cholesterol together with whole milk or standard or bifidus yogurt. The yogurts were fortified with skim milk powder, condensed whey or lactose-hydrolysed condensed whey. After 30 d, triacylglycerols, total cholesterol, HDL-cholesterol and LDL-cholesterol were measured in serum. Whole milk and ordinary yogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…This suggests that the inclusion of SMP in CLA diet reversed the rise in plasma cholesterol and TAG concentrations caused by CLA. The cholesterol lowering effect of milk and nonfat milk solids has been reported earlier also in rats (Oda and Hashiba 1994;Beena and Prasad 1997;Yadav et al 2006) and rabbits (Aggarwal and Kansal 1991). Therefore, the study implies that the effect of CLA on serum cholesterol is modified by other dietary ingredients, and milk is a better medium for delivery of CLA.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…This suggests that the inclusion of SMP in CLA diet reversed the rise in plasma cholesterol and TAG concentrations caused by CLA. The cholesterol lowering effect of milk and nonfat milk solids has been reported earlier also in rats (Oda and Hashiba 1994;Beena and Prasad 1997;Yadav et al 2006) and rabbits (Aggarwal and Kansal 1991). Therefore, the study implies that the effect of CLA on serum cholesterol is modified by other dietary ingredients, and milk is a better medium for delivery of CLA.…”
Section: Resultssupporting
confidence: 55%
“…Milk as well as non-fat milk solids have been previously reported to reduce serum cholesterol and triacylglycerols (Oda and Hashiba 1994;Beena and Prasad 1997;Aggarwal and Kansal 1991;Buonopane et al 1992;Yadav et al 2006;Cichosz 2007). Thus, the present study investigated the synergistic effect of CLA and non-fat milk solids on blood lipid profile under normocholesterolaemic dietary regimen.…”
Section: Introductionmentioning
confidence: 99%
“…First they promote structural integrity of the gastrointestinal barrier through its adhesive properties. When probiotics attach to enterocytes they "inhibit the binding of pathogens by a process of competitive exclusion (16)." Second they bind antigens, reducing their immunogenicity (17), and third they cause a reduction of inflammation of the gut by the balancing of pro vs. anti-inflammatory cytokines (1).…”
Section: Discussion the Effects Of Probiotics On The Gastrointestinalmentioning
confidence: 99%
“…Pfeuffer and Schrezenmier (2000) studied properties of milk bioactive substances and demonstrated that glycol-macro protein (GMP) derived peptides have antithrombotic activity. Beena and Prasad (1997) fed rats on yoghurt fortified with whey proteins, in the form of condensed and hydrolysed condensed whey, and found that whey proteins have marked effect on lowering of LDL cholesterol. They further found that whey proteins also lower liver cholesterol and significantly reduce plasma cholesterol by 35%.…”
Section: Type Of Proteinmentioning
confidence: 99%